A incidência do venire contra factum proprium nas relações de trabalho - Pessoa, Valton Doria (2013)
The purpose of this dissertation is to examine the impact of contradictory behavior under labor law, and how it relates to objective good faith. Contradiction is viewed as inherent to human behavior, whereby the limitations to inconsistent conducts are studied as a way to protect legitimate trust. Based on the study of objective good faith, as a limiter to the exercise of rights and its various forms of protection, there follows an attempt to defend the need for fair and ethical behavior in employment relationships, wherein the venire contra factum proprium lies -- the core of this study, in the employment context. Then the requirements of, and grounds for, venire are examined, as it is set apart from other doctrines pointed out by jurists, concerning the abusive exercise of rights. This is the necessary basis for the ensuing study on the application of venire to solve labor disputes, never failing to address its delicate conflict with the fundamental rights. The research continues by addressing the venire in employment relations; by analyzing its compatibility with labor law regulations and principles; the impact on individual and collective relations; and legal precedents. The results obtained from this study indicate that both companies and employees must abide, at all stages, in a given contract, by the trust that arises out of their initial behavior, thereby ensuring that the fair expectation stemming there from is not frustrated by any subsequent and contradictory conduct. Labor Law, despite its peculiarities, is not immune to the application of the venire contra factum proprium